Granular cell tumour of the breast: A rare presentation of a breast mass in an elderly female with a subsequent breast cancer diagnosis. (April 2019) - Al-Balas, Mahmoud; De Leo, Antonio; Serra, Margherita; Santini, Donatella; Taffurelli, Mario
A 74-year-old female patient presented with a hard breast mass and dimpling with a clinical suspicion of a carcinoma. Histological evaluation revealed a granular cell tumour. Granular cell tumour is a rare neoplasm, mostly benign in origin that may arise in every body site, 5%–15% of cases occur in the breast. It is strongly suggested that granular cell tumours origin is Schwann cells. Clinically, granular cell tumours presentation may mimic mammary carcinoma and their similar features on mammography and ultrasound make it difficult to differentiate between them.